Association of clinical knowledge with patient care ownership among resident physicians: a nationwide cross-sectional study in Japan - Hirohisa Fujikawa; Hidetaka Tamune; Yuji Nishizaki; Taro Shimizu; Yu Yamamoto; Kiyoshi Shikino; Miwa Sekine; Hiroyuki Kobayashi; Yasuharu Tokuda (BMC Medical Education)
Abstract Purpose Both clinical knowledge and patient care ownership (PCO) are crucial to the provision of quality patient care and should be acquired during training. However, the association between these two concepts is under-examined. Here, we conducted a nationwide cross-sectional study to investigate the association between clinical knowledge and PCO among resident physicians in Japan. Methods From January 17 to March 31, 2024, we conducted an anonymous, online, self-administered survey for a series of PCO research projects. The survey targeted medical residents who took the General Medicine In-Training Examination (GM-ITE). The mean of the Japanese version of the PCO Scale was used as outcome variable. The primary explanatory variable was total GM-ITE score, while the secondary explanatory variables were GM-ITE category scores in medical knowledge. We conducted multivariable linear regression analysis, controlling for postgraduate years, sex, number of assigned inpatients, weekly working hours, type of hospital, and size of hospital. Results We included 1836 participants in our statistical analysis. Multivariable linear regression analysis revealed that after adjustment for possible confounders, GM-ITE total scores showed a significantly negative association with PCO in the highest score quartile (adjusted mean difference − 0.20, 95% confidence interval (CI) -0.33 to -0.07, compared with the lowest score quartile). Additionally, after controlling for possible confounding factors, scores for symptomatology and clinical reasoning showed a dose-dependent negative association with PCO (adjusted mean difference − 0.17, 95% CI -0.30 to -0.03 for the highest score quartile compared with the lowest score quartile). No significant dose-dependent associations were found for the other categories. Conclusions These findings suggest the presence of potential challenges in the simultaneous fostering of clinical knowledge and PCO during residency training. This underscores the need for educators to actively engage in the reconsideration of current postgraduate training strategies, with the aim of effectively cultivating both clinical knowledge and PCO among medical residents.